1997
DOI: 10.1175/1520-0477(1997)078<2817:srrpwt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Shipboard Radar Rainfall Patterns within the TOGA COARE IFA

Abstract: Radar rainfall measurements over the equatorial western Pacific warm pool were collected by two shipboard Doppler radars as part of the Tropical Oceans Global Atmosphere Coupled Ocean-Atmosphere Response Experiment during the intensive observing period (November 1992-February 1993). A comprehensive dataset of gridded rainfall fields, convective/stratiform identification maps, and vertical structure products has been produced, covering an area approximately 400 km (E-W) by 300 km (N-S) within the Intensive Flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 56 publications
(70 reference statements)
5
90
0
Order By: Relevance
“…The quasiequilibrium assumptions on humidity and convective instability in model precipitation areas are used to assimilate TB's in rainy areas and rain flag data that are functions of precipitation. This assimilation was successful in producing model precipitation areas agreeing with the TOGA radar data given by Short et al (1997).…”
Section: Direct Assimilationmentioning
confidence: 99%
See 1 more Smart Citation
“…The quasiequilibrium assumptions on humidity and convective instability in model precipitation areas are used to assimilate TB's in rainy areas and rain flag data that are functions of precipitation. This assimilation was successful in producing model precipitation areas agreeing with the TOGA radar data given by Short et al (1997).…”
Section: Direct Assimilationmentioning
confidence: 99%
“…3) Assimilation of rain flag and TB's in rainy areas successfully produced model precipitation areas agreeing with radar observation data by Short et al (1997).…”
mentioning
confidence: 99%
“…Li and Gao (2011) calculated the linear correlation coefficient between simulated and observed rain rates, which is 0.45. The observational rain rates are derived by taking an average over a 150 × 150 km 2 area, which is based on radar reflectivity data taken from the Massachusetts Institute of Technology Doppler radar and the TOGA radar located within the IFA region (Short et al 1997). A Studentʼs t-test on the significance of the correlation coefficients shows that the critical correlation coefficient at the 1% significant level is 0.128.…”
Section: Model Experiment and Rain Microphysical Budgetmentioning
confidence: 99%
“…The entire series corresponds to the full period of Cruise 1 (November 10, 1992 through December 9, 1992), consisting of 1992 scans, and to the early part of Cruise 2 (December 21, 1992 through December 29, 1992), consisting of 617 scans. A good source of detailed information about TOGA-COARE and its objectives is Short et al [38]. The experience showed that the multiscaling analysis of wet and dry durations can be restricted to spatial scales ranging from 120 km down to 2 km, following the rule of half (approximately).…”
Section: Description Of Working Data and Related Issuesmentioning
confidence: 99%